Interior of Boston Coliseum, Copley Square, ca. 1872 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of the interior of the structure built for the National Peace Jubilee held in 1869. For the International Peace Jubilee of 1872, the interior is draped in bunting and seating is assembled. There are more than a dozen people including women in the foreground of the image. In the background musicians have assembled. Designed by William Gibbons Preston 10 x 13 15/16 overall 11 3/16 x 14 Photographs